DAYA DUKUNG HIJAUAN PAKAN DALAM KONSERVASI SAPI PUTIH TARO - I W. Suarna; M. A.P. Duarsa; N. P. Mariani; L. G. Sumardani; S. A. Lindawati (Environmental Research Center (PPLH) of Udayana University, 2016)
White cattle Taro is a Bali native germplasm that must be preserved in accordancewith the mandate of the Millennium Development Goals to reduce the rate of loss ofbiodiversity as a valuable genetic resources. At this time, the population of White cattleTaro is 34 heads, which the conditions still cause for concern because of the increasingpressure of various factors. When the white cattle graze in their natural habitat (forestTaro) White cattle Taro to reach a population of 150 animals (2001). Pressure againstwhite cow increasingly widespread because the land is narrow and increasing the amountof forage that should be provided in rotation by traditional society village of Taro. Tarovillage located in District Tegallalang, close to Districts Payangan Gianyar regency. Twodistricts are developing leading commodity Bali cattle. While White cattle Taro also requiresthe availability of forage species are the same as Bali cattle. The results showed that carryingcapacity of forage for White cattle Taro started to decline so that the necessary strategicapproach to the conservation of taro white cattle in order to accelerate the achievement ofthe millennium development. Such efforts are: 1) improving the efficiency of forageproduction 2) optimizing the utilization of forage 3) optimization of land use and cultivationof superior feed and 4) technological capacity building of local feed plant.